A family of acetato-diphenoxo triply bridged dimetallic ZnIILnIII complexes: SMM behavior and luminescent properties. Issue 23 (27th May 2016) - Oyarzabal, Itziar; Artetxe, Beñat; Rodríguez-Diéguez, Antonio; García, José Ángel; Seco, José Manuel; Colacio, Enrique
Abstract : A new family of Zn–Ln complexes that show interesting magnetic (SIM) and luminescent properties has been synthesized and characterized. Abstract : Eleven dimetallic Zn II –Ln III complexes of the general formula [Zn(µ-L)(µ-OAc)Ln(NO3 )2 ]·CH3 CN (Ln III = Pr (1 ), Nd (2 ), Sm (3 ), Eu (4 ), Gd (5 ), Tb (6 ), Dy (7 ), Ho (8 ), Er (9 ), Tm (10 ), Yb (11 )) have been prepared in a one-pot reaction from the compartmental ligand N, N ′-dimethyl- N, N ′-bis(2-hydroxy-3-formyl-5-bromo-benzyl)ethylenediamine (H2 L). In all these complexes, the Zn II ions occupy the internal N2 O2 site whereas the Ln III ions show preference for the O4 external site. Both metallic ions are bridged by an acetate bridge, giving rise to triple mixed diphenoxido/acetate bridged Zn II Ln III compounds. The Nd, Dy, Er and Yb complexes exhibit field induced single-ion magnet (SIM) behaviour, with U eff values ranging from 14.12 to 41.55 K. The Er complex shows two relaxation processes, but only the second relaxation process with an energy barrier of 21.0 K has been characterized. The chromophoric L 2− ligand is able to act as an "antenna" group, sensitizing the near-infrared (NIR) Nd III and Yb III -based luminescence in complexes2 and11 and therefore, both compounds can be considered as magneto-luminescent materials. In addition, the Sm III, Eu III and Tb III derivatives exhibit characteristic emissions in the visible region.